A link between two tumorigenic proteins, CD44 and p21WAF1: CD44 increases phorbol ester‐induced expression of p21WAF1 by stabilizing its mRNA and extending protein half‐life. Issue 16 (12th July 2013) - Lindner, Christina; Urbánek, Pavel; Pavelka, Birgit; Hartmann, Monika; Herrlich, Peter
Abstract : The cell surface glycoprotein CD44 enhances phorbol‐12‐myristate 13‐acetate (TPA)‐induced expression of p21 WAF1 by stabilizing its mRNA and enhancing the protein's half‐life in several cell lines. Only the plasma membrane‐anchored cytoplasmic tail of CD44 and its interacting ezrin, radixin, moesin (ERM) proteins are required for this effect. A mitogen activated kinase (MEK) inhibitor abolishes the action of CD44 on p21. Down‐regulation of p21 dramatically decreased anchorage‐independence of a cancer cell line, whereas CD44 expression in this background could partially rescue the phenotype. Abstract : We discovered that the glycoprotein CD44 enhances TPA‐induced expression level of p21 WAF1 . The increased p21 level is due to prolongation of the half‐life of p21 mRNA and protein. CD44 cannot increase p21 promoter activity. The plasma membrane anchored intracellular domain of CD44 (CD44ΔE) suffices to increase p21 level by interacting with ERM proteins and signal transduction through the Ras/MAPK pathway. p21 Downregulation dramatically reduced anchorage‐independence of a tumor cell line, whereas CD44 expression in this background partially rescued the phenotype.